COMPETITION BETWEEN TRIBOLIUM CASTANEUM (Herbst) AND TRIBOLIUM CONFUSUM (J. du Val.) IN LIMITED AMOUNT OF STANDARD MEDUMAND MAZE MEAL - ALLOTEY, J.; MOKHUNI, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
Competition between Tribolium castaneum (Herbst) and Tribolium confusum (J. du Val) was studied in limited amount of standard medium (maize meal-sorghum meal-glycerol) (8:8:l) (W/W) and maize meal; when the two species were reared separately (conditions Tcas and Tcon), when one was introduced before the other (conditions Tcas + Tcon/2 and Tcon + Tcas/2) and when both were introduced together (condition Tcas/Tcon) under ambient laboratory conditions (temperature range: 24-28°C, 61-77% R.H.). Separately, both T. castaneum and T. confusum thrived well in limited Supplies of the food media. T. castaneum was a better competitor than T. confusum when the two species existed together at the same time. However when one was introduced before the other, the first introduced species appeared to do better than the second species.